2022
DOI: 10.1108/ijchm-11-2021-1337
|View full text |Cite
|
Sign up to set email alerts
|

The antecedents of customer mistreatment: a meta-analytic review

Abstract: Purpose Frontline service employees are often subjected to customer mistreatment and considerable studies have tested outcomes of customer mistreatment. However, the importance of its antecedents is particularly underestimated. This meta-analytic paper aims to develop an overarching framework that identifies the antecedents of customer mistreatment as well as potential boundary conditions to account for observed variations reported in extant studies. Design/methodology/approach Comprehensive electronic and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 87 publications
0
19
0
Order By: Relevance
“…These findings highlight the importance of examining customer aggression from different perspectives. Past research from a between-person perspective has found that employees with high job autonomy may experience lower customer aggression overall, potentially because they use their autonomy to more effectively meet customer needs (see a meta-analytic review by Liu et al, 2022). Existing research has also shown that employees with high level of job autonomy may feel less threatened by aggressive customers (Grandey et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight the importance of examining customer aggression from different perspectives. Past research from a between-person perspective has found that employees with high job autonomy may experience lower customer aggression overall, potentially because they use their autonomy to more effectively meet customer needs (see a meta-analytic review by Liu et al, 2022). Existing research has also shown that employees with high level of job autonomy may feel less threatened by aggressive customers (Grandey et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Booyens et al (2022) called the ignorance of customer misbehavior a form of “social washing” and considered it crucial to investigate the hospitality industry's toxic organizational cultures and preventative measures. The recent studies by Huang and Kwok (2021) and Liu et al (2022) emphasized the uniqueness of examining customer mistreatment in service industries by focusing on the predictors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The paper by Liu et al (2022) titled “A systematic review of work-family enrichment in the hospitality industry” used 23 studies on work–family enrichment (WFE) published from 2000 to 2021 and systematically analyzed the articles following the guidelines of Preferred Reporting Items for Systematic reviews and Meta-Analyses. A framework was developed including the antecedents and outcomes of WFE at the organizational, job and individual levels.…”
Section: The Papers In This Special Issuementioning
confidence: 99%
“…In the last paper titled “The antecedents of customer mistreatment: A meta-analytic review,” Liu et al (2022) conducted a meta-analytic review to develop an overarching framework that identified the antecedents of customer mistreatment as well as potential boundary conditions. The study used 125 articles involving 141 independent samples.…”
Section: The Papers In This Special Issuementioning
confidence: 99%